Study of the impact of diesel generator sites on the local climate change of the city of Mosul using geographic information systems - Sabah Ali; Daoud Mohamed (College of Education for Pure Sciences, 2011)
Abstract Since the mid of 1990th, Mosul city over all Iraq cities, is used widely the local power diesel generators. The generators exhaust emits a large amounts of hydrocarbon gases, including, of course, carbon dioxide. In most cases, the Purity of the fuel (gas oil) is below the accepted standard purity. Certainly, the emission of large quantities of such hydrocarbon gases to the atmosphere, play an important role in contributing to global warming. Therefore, a significant bad side-effects influence Mosul city thermal balance and climate changes. Because the studied area is surrounded by Hills and highlands, therefore this topographic terrain leads to the precipitation of the exhaust generator output pollutants within the city air space, and leads to increase climate change which is reduce the green area proportion (i. e.; increasing the dryland spaces). Unfortunately, large proportions of local forest trees in the studied area, have been subjected to logging operations by citizens under the current circumstances for use as fuel. In this study, some treatments have been suggested to reduce further pollution emitting from the diesel generators. The aim is to reduce their negative effects on the environment, human health and land use. GIS software have been adopted in the current study (Global Mapper9, ArcGIS9.1) process and analyze the DEM data of the studied area with respect to satellite image to show the topographical features of the area and the location of the generators. GIS software also have been applied in the georeferncing process of the adopted remote sensing data. The descriptive approach has been adopted in the completion stages of the study in addition to the available data